(960) The Transportation Problem on the 1620 Digital Computer مشكلة النقل على جهاز الكمبيوتر ( الحاسوب الرقمي 1620) - Youssif Nasr El-Din.; Abd El-Hady Nabih. (معهد التخطيط القومى, 2024)
One of the earliest puplished accounts of a scientific method for formulating and solving distribution or transportation problems appeared in 1941. World war II subsequently saw considerable development of the techniques of linear programming and operations research. In 1951 considerable advance was given to linear programming by the Cowles commission.